Alternative synthesis of ZSM-5 using seeds and ethanol as co-template - Albiero, Jalusa Konzen; Coutinho, Elisa Barbosa; Schwaab, Marcio; Castilhos, Fernanda de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this work, it is proposed the ZSM-5 zeolite synthesis using crystals of this material as seeds and ethanol, substituting the usual nitrogenous organic bases as templates. The seeds were synthesized by the hydrothermal method employing n-butylamine as template. Using seeds and ethanol, as co-template, the synthesis of ZSM-5 was performed, having, as silica source, rice husk ash and, as aluminum source, kaolin. The zeolites were characterized by XRD, BET and FT-IR. The combination of seed and ethanol at different proportions resulted in the formation of ZSM-5 with high crystallinity, surface area up to 300 m2/g and micropores volume up to 0,114 cm3/g. Thus, it is evidenced thatnitrogen-containing templates can be satisfactorily replaced by the use of ZSM-5 seeds combined with ethanol.